2020
DOI: 10.1101/2020.03.18.986869
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

TMAO, a seafood-derived molecule, produces diuresis and reduces mortality in heart failure rats

Abstract: Background. There is an ongoing debate whether trimethylamine-oxide (TMAO), a molecule present in seafood and a derivate of microbiota metabolism, is beneficial or harmful for the circulatory system. Interestingly, deep-water animals accumulate TMAO that protects proteins such as lactate dehydrogenase (LDH) against high hydrostatic pressure. We hypothesized that TMAO may benefit the circulatory system by protecting cardiac LDH exposed to hydrostatic stress (HS) produced by contracting heart.Methods and Results… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 36 publications
0
7
0
Order By: Relevance
“…For example, TMAO reduced mortality in the SHHF mouse model, an effect associated with osmotic diuresis caused by the hyperosmotic state of TMAO. TMAO increased the level of vasopressin, in addition to its diuretic and natriuretic effects [28]. However, the study did not directly measure the blood pressure of mice, and the findings were contradictory to previous animal experiments, showing that TMAO upregulated the effect of AQP-2 and led to sodium and water retention by increasing plasma osmotic pressure, and amplified the boosting effect of Ang-II [11, 12], which may be related to variation in TMAO dosage and methods of intervention.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, TMAO reduced mortality in the SHHF mouse model, an effect associated with osmotic diuresis caused by the hyperosmotic state of TMAO. TMAO increased the level of vasopressin, in addition to its diuretic and natriuretic effects [28]. However, the study did not directly measure the blood pressure of mice, and the findings were contradictory to previous animal experiments, showing that TMAO upregulated the effect of AQP-2 and led to sodium and water retention by increasing plasma osmotic pressure, and amplified the boosting effect of Ang-II [11, 12], which may be related to variation in TMAO dosage and methods of intervention.…”
Section: Discussionmentioning
confidence: 99%
“…TMAO was initially thought to exist primarily in deep-sea fish and other aquatic products, functioning to maintain cell osmotic pressure and protect protein invariance. Eating these fish is thought to be good for the circulatory system [29-31], but animal experiments have shown that TMAO does not improve the prognosis of SHHF mice by affecting the structure of proteins such as lactate dehydrogenase [28].…”
Section: Discussionmentioning
confidence: 99%
“…In a recent report, it was suggested that the organic osmolyte function of TMAO induced diuresis when given at supraphysiologic levels, which led to improved heart failure outcomes. The investigators reported a primary diuretic effect in TMAO-fed rats ( 42 ). Interestingly, all the TMAO-fed rats (a different animal model compared with most TMAO studies) in this study also exhibited decreased plasma sodium with increased plasma renin, which is typically seen in worsened heart failure physiology.…”
Section: Discussionmentioning
confidence: 99%
“…TMAO has also been reported as a standby marker for some diseases, such as cardiovascular events (Guasti et al, 2021;Janeiro et al, 2018). While most studies of TMAO have focused on its role in and/or association with cardiovascular disease (Dannenberg et al, 2020;Gawrys-Kopczynska et al, 2020;Guasti et al, 2021;Janeiro et al, 2018;Mafune et al, 2016;Poll et al, 2020;Querio et al, 2019;, TMAO has also been reported to be associated with kidney disease (Gruppen et al, 2017;Rhee et al, 2013;Sun et al, 2017;Tang et al, 2015). Rhee et al reported that the baseline plasma levels of TMAO and its precursor choline are predictors of CKD in the cohort of the Framingham Heart Study who did not have CKD at baseline (Rhee et al, 2013).…”
Section: Inhibition Of Tmao Production Attenuates Adenine-induced Ren...mentioning
confidence: 99%
“…In contrast, TMAO has been reported to benefit or at least not harm health. For example, Stubbs et al reported no evidence linking TMAO to clinical cardiovascular outcomes in patients with end-stage kidney disease (Stubbs et al, 2019), and TMAO reduced mortality in rats with heart failure (Gawrys-Kopczynska et al, 2020). TMAO has also been reported as a standby marker for some diseases, such as cardiovascular events (Guasti et al, 2021;Janeiro et al, 2018).…”
Section: Inhibition Of Tmao Production Attenuates Adenine-induced Ren...mentioning
confidence: 99%